The Effect of Using Kim’s Memory Game towards Students’ Speaking Skill - Riandi Riandi; Leni Suryani (Journal of English Education Studies, 2018)
This study aims to determine the effect of using Kim’s memory game towards students’ speaking skill at tenth grade students of SMAN 1 Malingping–Lebak under this research question: is there any effect of using Kim’s memory game towards students’ speaking skill?. The method used in this research is an experimental research. the population was taken 319 and sample 34 for experimental class and 34 for control class. The researcher uses English oral test (pre-test and post-test) as instrument of the research before and after giving treatment to each class, control and experimental class. From the result of the research, the researcher found that the students in experimental class got better result than those in control class. This can be seen from the data showed that t test (t0) is 3.17, while t table (tt) is 2.00, in other words t test > t table. This means that there is significant effect of Kim’s memory game in teaching speaking. So the hypothesis alternative (Ha) is accepted.